2018
DOI: 10.1080/02646838.2018.1490496
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic coping and dyadic adjustment in couples with women with high depressive symptoms during pregnancy

Abstract: These findings highlight the need to assess couples' dyadic adjustment and DC strategies, which is particularly important when women screened positive for high levels of depressive symptoms during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 27 publications
4
20
0
1
Order By: Relevance
“…Overall, our findings revealed that DC seems to be an important factor for couples who are expecting a baby, given its potential impact on both marital adjustment and quality of life. As found in previous studies, DC contributes to improve marital adjustment (Alves et al, 2018;Molgora et al, 2018) as well as quality of life (Calou et al, 2018;Elsenbruch et al, 2006), for both women and men. Our results align with a previous study conducted with pregnant women and their partners, in which own common DC was associated with the partners' marital adjustment (Molgora et al, 2018).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Overall, our findings revealed that DC seems to be an important factor for couples who are expecting a baby, given its potential impact on both marital adjustment and quality of life. As found in previous studies, DC contributes to improve marital adjustment (Alves et al, 2018;Molgora et al, 2018) as well as quality of life (Calou et al, 2018;Elsenbruch et al, 2006), for both women and men. Our results align with a previous study conducted with pregnant women and their partners, in which own common DC was associated with the partners' marital adjustment (Molgora et al, 2018).…”
Section: Discussionsupporting
confidence: 66%
“…Thus, our findings suggest that DC was associated with higher levels of marital adjustment, which in turn were associated with better quality of life. It seems that when women and men are able to employ DC strategies to deal with pregnancy-related changes, they become more satisfied with their marital relationship (Alves et al, 2018;Molgora et al, 2018) which contributes to their wellbeing (Figueiredo et al, 2008;Gameiro et al, 2011). Moreover, women's quality of life seems to be more dependent on the way their partners deal with this stressful life event, since an indirect partner effect was found from men's DC to women's quality of life via women's marital adjustment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, we did have more variance and a higher severity of depressive symptoms for women in our sample. A bidirectional association cannot be precluded, insofar as more depressed women would be less likely to provide a lot of support [71]. Especially in women with high levels of depression, lower provided dyadic coping was found [72].…”
Section: Discussionmentioning
confidence: 94%
“…One possible explanation for our findings is that pregnancy is a predominant woman‐centered phase, during which women experience more physical changes and are particularly vulnerable to emotional fluctuations (Hodgkinson, Smith, & Wittkowski, ; Staneva, Bogossian, & Wittkowski, ) compared to men. This can explain why, compared to men, pregnant women are more likely to communicate stress to their partners (Alves, Fonseca, Canavarro, & Pereira, 2018b; Molgora et al., ), their well‐being is positively influenced by their partner's DC (Brandão et al., ) while negatively affected (at early postpartum) when women engage in positive DC behaviors towards their male partner's needs during pregnancy (Alves et al, ). Thus, perceiving complementary (as opposed to similar) exchanges in DC during pregnancy is likely to better fit each partner's needs of support and hence have more positive effects in the long term.…”
Section: Discussionmentioning
confidence: 99%